2022
DOI: 10.3390/nu14235185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Associations between MIND and Mediterranean Diet Scores with Patient-Reported Outcomes in Parkinson’s Disease

Abstract: The Mediterranean (MEDI) and Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diets have been associated with a reduced risk of Parkinson’s disease (PD) diagnosis. However, studies evaluating whether these diets are associated with disease progression in those patients already diagnosed are lacking. The objective of this study was to evaluate whether MIND and MEDI scores were associated with improved patient-reported outcomes. Additionally, we sought to explore which questions on the MIND and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The PRO-PD score significantly decreased by 25.6 points per one point increase in Mediterranean diet score and by 52.9 points per point increase in MIND diet score. Thus, while both diets decreased the severity of PD symptoms, the benefit of the MIND diet was more robust which was consistent with prior studies ( Fox et al., 2022 ).…”
Section: The Gut Microbiotasupporting
confidence: 91%
“…The PRO-PD score significantly decreased by 25.6 points per one point increase in Mediterranean diet score and by 52.9 points per point increase in MIND diet score. Thus, while both diets decreased the severity of PD symptoms, the benefit of the MIND diet was more robust which was consistent with prior studies ( Fox et al., 2022 ).…”
Section: The Gut Microbiotasupporting
confidence: 91%
“…An inappropriate dietary pattern is closely related to increased in ammatory factors in PD, which are often caused by oxidative stress and chronic neuroin ammation [5,6] . There has been some research suggesting that a Western diet increases in ammation factors, which are associated with a higher risk of PD, while Mediterranean diets are associated with lower ones, which have protective effects against PD onset and progression [6][7][8][9][10] . It is an effective method for measuring a diet's in ammatory potential known as the Dietary In ammation Index [5,11] .…”
Section: Introductionmentioning
confidence: 99%
“…The MIND diet combines principles from the MeDi and Dietary Approaches to Stop Hypertension diet, originally developed to reduce cognitive decline [26]. The MIND encourages leafy greens, bean and berry consumption and discourages cheese, butter and margarine intake [27]. A longitudinal study of 706 aging American adults found that MIND diet adherence was associated with reduced incidence and slower progression of parkinsonism relative to MeDi diet adherence [28], while a Canadian crosssectional study found that MIND diet adherence was associated with a higher age at PD onset of up to 17.4 years (p < 0.001) specifically in females [18].…”
Section: Mind Dietmentioning
confidence: 99%